D and E region incoherent scatter radar density measurements over Jicamarca - Chau Chong Shing, Jorge Luis (2005)
We present the first daytime E and D region incoherent scatter radar (ISR) measurements of electron densities at equatorial latitudes, using the Jicamarca ISR. Both measurements have been obtained using a high-resolution ISR mode with a relatively short interpulse period. Usually, E region ISR measurements are not feasible due to the clutter caused by strong echoes from equatorial electrojet irregularities (EEJ). Our E region ISR measurements were possible during an event when EEJ echoes were absent and show an excellent agreement with an empirical model based on rockets measurements (FIRI). In addition, we show that the employed high resolution mode also works to get densities between 130 and 200 km even during strong EEJ events, a region that is poorly known. In the case of D region densities, normally they are difficult to obtain due to the presence of strong coherent echoes caused by mesospheric turbulent layers. Fortunately, these layers are usually organized in narrow regions; therefore using a high range resolution, we have been able to get weak signals from the regions in between the layers causing coherent echoes. Our preliminary results show that our D region density estimates are in reasonable agreement with empirical models, in some cases providing slightly larger values. These new D region estimates contain important geophysical information that we plan to explore in the future.